A Managerial Decision Model of International Cooperative Venture Formation - Tallman, Stephen B.; Shenkar, Oded (Journal of International Business Studies, 1994)
This paper develops a model of international cooperative venture formation that is centered on the decisionmaking process of MNE executives. Central issues for managerial decisions are developed from the organizational studies literature. A framework delineating the sequence and criteria used in the decision to form international cooperative ventures is developed from these defined issues and from existing models. Propositions pertaining to the venture formation decision process are outlined.